Atypical chromosome 22q11.2 deletions are complex rearrangements and have different mechanistic origins. (13th July 2019) - Vervoort, Lisanne; Demaerel, Wolfram; Rengifo, Laura Y; Odrzywolski, Adrian; Vergaelen, Elfi; Hestand, Matthew S; Breckpot, Jeroen; Devriendt, Koen; Swillen, Ann; McDonald-McGinn, Donna M; Fiksinski, Ania M; Zinkstok, Janneke R; et al.
Abstract: The majority (99%) of individuals with 22q11.2 deletion syndrome (22q11.2DS) have a deletion that is caused by non-allelic homologous recombination between two of four low copy repeat clusters on chromosome 22q11.2 (LCR22s). However, in a small subset of patients, atypical deletions are observed with at least one deletion breakpoint within unique sequence between the LCR22s. The position of the chromosome breakpoints and the mechanisms driving those atypical deletions remain poorly studied. Our large-scale, whole genome sequencing study of >1500 subjects with 22q11.2DS identified six unrelated individuals with atypical deletions of different types. Using a combination of whole genome sequencing data and fiber-fluorescence in situ hybridization, we mapped the rearranged alleles in these subjects. In four of them, the distal breakpoints mapped within one of the LCR22s and we found that the deletions likely occurred by replication-based mechanisms. Interestingly, in two of them, an inversion probably preceded inter-chromosomal 'allelic' homologous recombination between differently oriented LCR22-D alleles. Inversion associated allelic homologous recombination (AHR) may well be a common mechanism driving (atypical) deletions on 22q11.2.